Acute angle closure glaucoma: relative failure of YAG iridotomy in affected eyes and factors influencing outcome. Issue 7 (July 1994) - Buckley, S A; Reeves, B; Burdon, M; Moorman, C; Wheatcroft, S; Edelsten, C; Benjamin, L
Abstract : The treatment of acute angle closure glaucoma has been influenced by the development of the YAG laser and its ability to perform iridotomies as an outpatient procedure. In this retrospective study the results of YAG iridotomy were compared with surgical peripheral iridectomy. When compared with surgical peripheral iridectomy patients, YAG iridotomy patients were at greater risk of proceeding to further surgery, with this risk being significantly associated with increasing duration of attack. The authors suggest that in selected cases, surgical iridectomy should be given consideration as a primary procedure.